Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content:1. The role of Flexibility-Building Techniques in The development of Administrative processes and Performance Management from The perspective of the administrative staff at Tabuk UniversityDr. Najwa Mufawez Mofeez Al-Fawaz2. The Role of Human Resource Management in Enhancing Positive Psychological Capital among Employees in Government Sector in Saudi Arabia in light of Vision 2030, in Riyadh Sarah Hamoud Al-Hamali Al-Qahtani , Sarah Mubarak Al-Dosari, Amal Abbas Al-Tawili3. The impact of Lean management on achieving Functional Creativity, an applied study at Taif UniversityDr. Samia Ayed Al-Jaeed, Remas Ahmad Al-Thbaity4. A Proposal to Activate the Collective Waqf Platform Using the Blockchain Platform - Jordan as an Example -Qusai Mahmoud Sindyani, Bayan Zuhier Ababneh5. Banking Merger, Challenges & Its Impact on the Financial Performance of Sudanese Banks: Empirical Study- Blue Nile Mashreq Bank (2015-2020)Dr. Omer Ali Babiker El-Tahir
Keywords: Journal of Economic, Administrative and Legal Sciences